Answer:
9y(2x - 1)(x - 2y)(x + 2y)
Step-by-step explanation:
Given
18x³y - 9x²y - 72xy³ + 36y³ ← factor out 9y from each term
= 9y(2x³ - x² - 8xy² + 4y²)
Factor the first/second and third/fourth term in the parenthesis
= 9y( x²(2x - 1) - 4y²(2x - 1)) ← factor out (2x - 1) from each term
= 9y(2x - 1)(x² - 4y²)
x² - 4y² is a difference of squares and factors in general as
a² - b² = (a - b)(a + b), thus
x² - 4y²
= x² - (2y)² = (x - 2y)(x + 2y), hence
18x³y - 9x²y + 72xy³ + 36y³
= 9y(2x - 1)(x - 2y)(x + 2y) ← in factored form
Answer:
the answer to the first question is 9/27, 5/27, 13/27
the answer to the second question is 27/126, 33/126, 20/126, 42/126
the answer to the last question is 32/44
Step-by-step explanation:
they way you solve the fist two questions you just add the numbers up and that will tell you your probability.
for the last question you take the number of players and subtract it by 12 to get the top number
The given expression is undefined when x = 5 OR x = -5
<h3>Undefined expression </h3>
From the question, we are to determine the value of x for which the given expression is undefined
The given expression is
x-4/3x²-75
An expression is undefined when the denominator equals zero
Thus, the expression is undefined when
3x² - 75 = 0
Now, we will determine the values of x in the equation above
3x² - 75 = 0
3x² = 75
x² = 75/3
x² = 25
x = ±√25
x = ±5
Hence, the given expression is undefined when x = 5 OR x = -5
Learn more on Undefined expression here: brainly.com/question/19815575
#SPJ1
the answer is -35/66
to divide fractions you take the reciprocal of the second fraction (switching the numerator and denominator) and multiply it so the equation turns into
5/6*(-7/11) = -35/66
hope you understand now
Answer:
7 6/18
Step-by-step explanation: